The Borromean Knot and Discourse Theory. Proposals for the Analysis of Identities, Phenomena and Sociopolitical Processes - Fair, Hernán (Foro Interno, 2021)
This paper explores innovative uses of the figure of the Borromean knot in lacanian theory with the aim of strengthening social research from a political discourse analysis approach. The first part of this paper: (a) distinguishes three discursive modalities of Borromean knot that intertwine the Real, the Symbolic and the Imaginary at a spatial and temporal level; (b) distinguishes between types of knotting, their extension, intensity and time of structuring and social sedimentation; (c) analyses the dynamic of Borromean (un) knotting of the Real, Symbolic and Imaginary, through imaginary modes of identification in ideological fantasies, deeply dislocating events, and symptoms that symbolize the Real through the significant order. In the second part, several useful analytical strategies for the study of identities, phenomena and sociopolitical processes are proposed and illustrated with examples. In the last part, the epistemological and axiological implications of the use of this lacanian tool to strengthen critical social research from the Political Theory of Discourse are examined.
Keywords: Borromean knot; knotting between Real, Symbolic and Imaginary; ideological fantasy; symptom; lacanian theory